The impact of participation in ERASMUS study abroad in the UK on students’ overall English language proficiency, self-efficacy, English use anxiety and self-motivation to continue learning English: a mixed methods investigation - Hessel, G (2016)
It is widely assumed that participation in study abroad contributes to developing second language (L2) proficiency, as well as related outcomes such as higher levels of L2 learning motivation and intercultural competence. However, empirical studies into the outcomes of participation in study abroad have been affected by a series of methodological limitations, including complete reliance on participant self-assessment, the omission of longitudinal design elements, failure to control for non-equivalent comparison groups where these are included and insufficient sample sizes for testing programme effects. Thus, the present study investigates further the impact of studying abroad with the EU's ERASMUS programme on the participants' overall L2 proficiency, their self-efficacy and anxiety in using the L2 with native and non-native speakers and on their self-motivation to continue learning the L2. To this end, a longitudinal mixed methods design was employed in which 143 German university students who applied for an ERASMUS exchange with a British university for the academic year 2012-2013 and were either accepted or rejected/ withdrawn formed the abroad and comparison groups. All students completed C-tests of overall English language proficiency and questionnaires that inquired into the students' mobility history, their L2 learning background, L2 motivation, intergroup attitudes and aspects of the study abroad experience itself. Both instruments were administered online at the onset of the study abroad period (September 2012), one term into the programme (December 2012) and prior to the students' return (either December 2012 or June 2013). This predominantly quantitative group-level study served to establish the outcomes of participation in study abroad for the students' linguistic and motivational development. Repeated interviews with a sub-sample of 15 participants served to illuminate the observed outcome patterns in terms of the motivational dynamics during study abroad, as well as common factors associated with individual differences in linguistic development. The results of the study show that during the first 3 months abroad the ERASMUS students made significantly higher gains in overall English proficiency than the group of potentially mobile students who continued to study at home. The effect of the learning context was large and highly significant (p =.001), even after the influence of pre-existing participant characteristics on the students’ proficiency development was controlled for. During the subsequent 6 months of the study abroad period, however, progress among the ERASMUS group slowed and the between-group differences were no longer significant. The participants' L2 proficiency level at programme entry emerged as the strongest predictor of overall L2 proficiency gain, explaining up to 31.5% of the variance. The students’ attitudes towards their own national group, their perceptions of self-efficacy and feelings of anxiety when using English in social interactions, the perceived present-future L2 self-discrepancy and gender explained another 13.6% of the variance in overall L2 proficiency gain. Learner-external factors, including participation in English language instruction, participation in clubs and societies, the number of academic contact hours and type of enrolment, and free time spent with co-national peers, including friends and family back home explained a further 10.9%. The qualitative analysis of the students’ accounts provided further insights into the ways in which these factors play out in L2 learning abroad, as well as into the students’ perceptions of aspects of studying abroad that contributed most to their linguistic development. Regarding the motivational impact of the study abroad experience, the study found that ERASMUS students tended to develop significantly higher levels of self-efficacy in using English in social interactions as compared to the group of potentially mobile students who continued to study at home, while both the levels of perceived present-future self-discrepancy and English use anxiety with native and non-native speakers fell during the first 3 months abroad. While the overall impact of the study abroad experience on the students' motivation to continue learning the L2 was perceived as positive by the vast majority of participants, a decline in learning motivation was observed for most students after the initial 3-month period. The qualitative analysis showed that this decline can be plausibly explained by developments in the students’ English self-concept that occurred in response to the study abroad experience. Evidence-based recommendations are made regarding ways in which the linguistic and motivational development of ERASMUS students can be more effectively supported by higher education institutions.